Selective IL-23 Inhibition by Risankizumab Modulates the Molecular Profile in the Colon and Ileum of Patients With Active Crohn's Disease: Results From a Randomised Phase II Biopsy Sub-study. (19th July 2018) - Visvanathan, Sudha; Baum, Patrick; Salas, Azucena; Vinisko, Richard; Schmid, Ramona; Grebe, Kristie M; Davis, Justin W; Wallace, Kori; Böcher, Wulf O; Padula, Steven J; Fine, Jay S; Panés, Julián
Abstract: Background and Aims: We aimed to investigate the underlying mechanism of action of risankizumab, a monoclonal antibody targeting the IL-23 p19 subunit, previously reported to induce clinical and endoscopic remission in a randomised phase II study in patients with active Crohn's disease. Methods: Ileum and colon biopsies obtained at screening and Week 12 from a subgroup of patients [ n = 106] in the risankizumab phase II study were analysed by transcriptome-wide RNA-Seq profiling. Univariate associations were assessed using linear modelling. Results: By Week 12, risankizumab significantly decreased [ p < 0.005] the expression of 1880 and 765 genes in the colon [false-discovery rate = 0.02] and ileum [false-discovery rate = 0.05], respectively. These genes were associated with the IL-23/IL-17 axis, Th1 pathway, innate immunity, and tissue turnover. Colonic transcriptomic profiles following risankizumab treatment reflected the transcriptomic changes observed in patients achieving endoscopic response and remission at Week 12 and were significantly different from placebo [ p < 0.005]. The colonic transcriptomic profile, significantly modulated by risankizumab at Week 12, was indicative of suppression of pathways associated with epithelial biology. Furthermore, pathways associated with Crohn's disease modulated by risankizumab treatment included second messenger-mediated signalling, immune response, lymphocyte and leucocyte activation, lymphocyte differentiation and cell–cell adhesion. Conclusions: Endoscopic remission and response observed with risankizumab in patients with active Crohn's disease was associated with significant transcriptomic changes in the colon, compared with placebo. Differentiated expression of genes associated with the IL-23/IL-17 axis was observed in the colon and ileum 12 weeks after risankizumab treatment.